2008
DOI: 10.1093/nar/gkm1068
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae HMO1 interacts with TFIID and participates in start site selection by RNA polymerase II

Abstract: Saccharomyces cerevisiae HMO1, a high mobility group B (HMGB) protein, associates with the rRNA locus and with the promoters of many ribosomal protein genes (RPGs). Here, the Sos recruitment system was used to show that HMO1 interacts with TBP and the N-terminal domain (TAND) of TAF1, which are integral components of TFIID. Biochemical studies revealed that HMO1 copurifies with TFIID and directly interacts with TBP but not with TAND. Deletion of HMO1 (Δhmo1) causes a severe cold-sensitive growth defect and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 81 publications
5
48
0
Order By: Relevance
“…A number of transcription factors have been reported to contribute to the regulation of RP gene activity, including Rap1p, which binds the majority of RP genes and forms nucleosome-free regions in target promoters (155,166). HMO1 binds RP gene promoters with variable occupancy and has been implicated in preinitiation complex (PIC) assembly by covering a nucleosome-free region and in the recruitment of the transcription factor Fhl1p (forkhead like) (149,150,155,167,168).…”
Section: Hmo1 Regulates Pol II Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of transcription factors have been reported to contribute to the regulation of RP gene activity, including Rap1p, which binds the majority of RP genes and forms nucleosome-free regions in target promoters (155,166). HMO1 binds RP gene promoters with variable occupancy and has been implicated in preinitiation complex (PIC) assembly by covering a nucleosome-free region and in the recruitment of the transcription factor Fhl1p (forkhead like) (149,150,155,167,168).…”
Section: Hmo1 Regulates Pol II Transcriptionmentioning
confidence: 99%
“…The TAF1 N-terminal domain (TAND) inhibits the binding of TBP to the TATA element (169); it has been reported that HMO1 interacts with TBP and TAND and that HMO1 deletion decreases the transcription of TAND-dependent genes, suggesting that HMO1 prevents inhibitory TBP-TAND interactions. In addition, an interaction between HMO1 and TFIID was suggested by the observation that HMO1 deletion causes an upstream shift in transcription start sites of genes under the control of HMO1-enriched promoters but not of genes under the control of promoters with limited HMO1 occupancy (168). This shift in the transcriptional start site was subsequently linked to the ability of HMO1 to mask a nucleosome-free region to prevent inappropriate PIC assembly (167).…”
Section: Hmo1 Regulates Pol II Transcriptionmentioning
confidence: 99%
“…TSSs were analyzed by primer extension analysis as described previously. 19) The TK3212 (endogenous RPS5) and KK288 (RPS5*p+HIS3 reporter) primers were used for the analysis. Electrophoretic images were acquired by exposing gels to imaging plates, and were analyzed by image analyzer BAS2500 (Fuji Film).…”
Section: Tss Shift Screeningmentioning
confidence: 99%
“…15) Immunoprecipitation was performed using Dynabeads Protein G (Invitrogen) and an anti-FLAG monoclonal antibody (Sigma-Aldrich; M2) or anti-Hmo1 polyclonal antibody. 19) Real-time quantitative PCR analyses were performed using the KAPA SYBR FAST qPCR Kit (Kapa Biosystems) and the Mx3000P qPCR System (Agilent Technologies). Each experiment was performed in triplicate and the mean and standard deviations of the ratio of immunoprecipitated DNA to input DNA (IP/input) were calculated.…”
Section: Chip Assaymentioning
confidence: 99%
See 1 more Smart Citation